Miniaturized stacked implant antenna design at ISM band with biocompatible characteristics. Issue 4 (6th July 2015) - Kaka, Ademola O.; Toycan, Mehmet; Walker, Stuart D.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – A vertically stacked, three layer hybrid Hilbert fractal geometry and serpentine radiator-based patch antenna is proposed and characterized for medical implant applications at the Industrial, Scientific and Medical band (2.4-2.48 GHz). Antenna parameters are optimised to achieve miniaturized, biocompatible and stable transmission characteristics. The paper aims to discuss these issues. Design/methodology/approach – Human tissue effects on the antenna electrical characteristics were simulated with a three-layer (skin, fat and muscle) human tissue model with the dimensions of 180×70×60 mm3 (width×height×thickness mm3). Different stacked substrates are utilized for the satisfactory characteristics. Two identical radiating patches are printed on Roger 3, 010 (εr=10.2) and Alumina (εr=9.4) substrate materials, respectively. In addition, various superstrate materials are considered and simulated to prevent short circuit the antenna while having a direct contact with the metallization, and achieve biocompatibility. Finally, superstrate material of Zirconia (εr=29) is used to achieve biocompatibility and long-life. A finite element method is used to simulate the proposed hybrid model with commercially available Ansoft HFSS software. Findings – The antenna is miniaturized, having dimensions of 10×8.4×2 mm3 (width×height×thickness mm3). The resonance frequency of the antenna is 2.4 GHz with a bandwidth of 100 MHz at return loss (S11) of better than −10 dB characteristics. Overall, the proposed antenna have 50 Ω impedance matching, −21 dB far field antenna gain, single-plane omni-directional radiation pattern properties and incident power of 5.3 mW to adhere Specific Absorption Rate regulation limit. Originality/value – Vertically stacked three layer hybrid design have miniaturized characteristics, wide bandwidth, biocompatible, and stable characteristics in three layer human tissue model make this antenna suitable for implant biomedical monitor systems. The advanced simulation analysis of the proposed design constitutes the main contribution of the paper.